Identification of Chloride Intracellular Channel Protein 3 as a Novel Gene Affecting Human Bone Formation. (28th April 2017) - Brum, Andrea M; van der Leije, Cindy S; Schreuders‐Koedam, Marijke; Verhoeven, Jeroen; Janssen, Mark; Dekkers, Dick HW; Demmers, Jeroen AA; Eijken, Marco; van de Peppel, Jeroen; van Leeuwen, Johannes PTM; van der Eerden, Bram CJ
ABSTRACT: Osteoporosis is a common skeletal disorder characterized by low bone mass leading to increased bone fragility and fracture susceptibility. The bone building cells, osteoblasts, are derived from mesenchymal stromal cells (MSCs); however, with increasing age osteogenic differentiation is diminished and more adipocytes are seen in the bone marrow, suggesting a shift in MSC lineage commitment. Identification of specific factors that stimulate osteoblast differentiation from human MSCs may deliver therapeutic targets to treat osteoporosis. The aim of this study was to identify novel genes involved in osteoblast differentiation of human bone marrow–derived MSCs (hMSCs). We identified the gene chloride intracellular channel protein 3 ( CLIC3 ) to be strongly upregulated during MSC‐derived osteoblast differentiation. Lentiviral overexpression of CLIC3 in hMSCs caused a 60% increase of matrix mineralization. Conversely, knockdown of CLIC3 in hMSCs using two short‐hairpin RNAs (shRNAs) against CLIC3 resulted in a 69% to 76% reduction in CLIC3 mRNA expression, 53% to 37% less alkaline phosphatase (ALP) activity, and 78% to 88% less matrix mineralization compared to scrambled control. Next, we used an in vivo human bone formation model in which hMSCs lentivirally transduced with the CLIC3 overexpression construct were loaded onto a scaffold (hydroxyapatite‐tricalcium‐phosphate), implanted under the skin of NOD‐SCID mice, and analyzed for bone formation 8 weeks later. CLIC3 overexpression led to a 15‐fold increase in bone formation (0.33% versus 5.05% bone area relative to scaffold). Using a Clic3‐His‐tagged pull‐down assay and liquid chromatography–mass spectrometry (LS/MS)‐based proteomics analysis in lysates of osteogenically differentiated hMSCs, we showed that CLIC3 interacts with NIMA‐related kinase 9 (NEK9) and phosphatidylserine synthase 1 (PTDSS1) in vitro, and this finding was supported by immunofluorescent analysis. In addition, inhibition of NEK9 or PTDSS1 gene expression by shRNAs inhibited osteoblast differentiation and mineralization. In conclusion, we successfully identified CLIC3 to be a lineage‐specific gene regulating osteoblast differentiation and bone formation through its interaction with NEK9 and PTDSS1. © The Authors. JBMR Plus is published by Wiley Periodicals, Inc. on behalf of the American Society for Bone and Mineral Research.